Write to the Top! - Johnson, W. author. aut Link
XVI, 200 p.
Keywords: This is a pithy, no-nonsense, no-excuses guide to maximizing the quality and quantity of your scholarly products. Write to the Top! offers an accessible overview of the art of writing efficiently and effectively; it is the first book that explicitly summarizes the key elements to prolific productivity in academic settings.